STATIC THREE-DIMENSIONAL RESERVOIR MODELING AND ANALYSIS OF FACIES RELATION TO PETROPHYSICAL ROCK TYPE (PRT) ON RS-04 SANDSTONE RESERVOIR, MUTI FIELD, SANGASANGA BLOCK, KUTAI BASIN, EAST KALIMANTAN - GIGA SAKTI (NIM: 22014038), KURNIAWAN
Muti Field is a gas field located on the eastern edge of East Kalimantan Island, which produces hydrocarbons in the RS-04 interval reservoir of Balikpapan Grub. The discovery of hydrocarbons at Muti Field began in 1982 and produced in 1991. Muti Field is currently in development stage. Thus, it requires a more comprehensive reservoir model for further development strategies. This study uses various data consisting of rock core data with a total length of 134.9 feet, 8 samples of thin incision, wire rope record data of 52 wells, and 3D seismic data. The first step in the research is to identify litofasies and facies associations to determine the deposition environment. Based on the analysis of core rock and electrophasies, the study area has three facies associations, including distributary channel, interdistibutary, and crevasse splay. Based on the results of core rock analysis, it is known that RS-04 sandstone reservoir belongs to the distributary channel facies and is composed of eight litofasies; Litofasies structureless medium – fine sandstone (Ssl), medium – fine planar cross lamination sandstone (Sp), biortubation very fine-medium sandstone (Sb), broad, shallow scour granules – medium sandstone (Ss), horizontal lamination very fine-medium sandstone (Sh), wavy lamination fine sandstone (Sw), Clay stone (Fl). Three-dimensional reservoir characterization performed through facies modeling, rock type, shale volume, porosity modeling, and permeability modeling. Sandstone distributary channel deposits in the study area can be divided into three rock type (RT); RT 1, RT 2, and RT 3, each rock type has a good porosity and permeability connection. In addition, it can be seen that a facies association may consist of several rock types and one rock type may be composed of several lithofasies in RS-04 sandstones.